Prevalence and Treatment Outcome of Displaced High-Long Oblique Supracondylar Humeral Fractures in Children - Shah, Mudit; Han, Joo Hyung; Park, Hoon; Kim, Hyun Woo; Park, Kun-Bo (Frontiers in Pediatrics, 2021)
Aim: The treatment protocol for supracondylar humeral fracture has mainly been based only on the severity of displacement and percutaneous pinning has been recommend as a first treatment. However, a long oblique fracture line is difficult to fix by the traditional cross pinning. The purpose of this study is to assess the prevalence of high-long oblique supracondylar humeral (HLO) fracture and evaluate the surgical outcome of percutaneous pin fixation. Methods: We reviewed 690 children who had undergone an operation for the displaced supracondylar humeral fracture. HLO fracture was defined as having a fracture line starting from either cortex above the metaphyseal-diaphyseal junction and finishing at the opposite cortex around or below the olecranon fossa. Clinical and radiographic parameters outcomes were assessed. Results: Fourteen patients were diagnosed with the HLO fracture (14/690) and all the patients were treated by pin fixation. The median age was five years one month (range, 2–11 years). The common mode of injury was direct contact injury to the elbow. There were 6 patients with lateral HLO fracture, and 8 patients had medial HLO type. In medial HLO type, medial pinning only was done in 3 patients due to the difficulty in lateral pin insertion. And the lateral pin was not a bicortical fixation through capitellum entry in 2 patients who had fixed by cross pinning. The final Baumann angle and lateral humero-capitellar angle were 20.5 (5-67.6) degrees and 49.3 (23.3-71.9) degrees, respectively, without statistical significance compared to the normal side. Flynn's cosmetic grade showed satisfactory results in all patients. Conclusion: The prevalence of HLO fractures was 2% in the displaced supracondylar humeral fracture. The mechanism of injury of HLO fractures may be direct contact injury. In medial HLO fractures, medial pinning is important for stability, and sometimes lateral pinning was impossible. Contrarily, lateral HLO fracture could easily be fixed by lateral-only pinning, but the correct lateral pinning is necessary because medial pinning is difficult. The HLO fracture is a difficult pattern to treat by traditional percutaneous pinning and another surgical option should be considered.